The effect of varying amounts of antibiotics (Aureomycin-B12 supplement) in the protein supplement for swine on sudan pasture. - Aubel, C.E. (Kansas Agricultural Experiment Station, 2012)
In recent years the use of antibiotics in swine nutrition has received much attention. Research has shown that different vitamin B12 antibiotic supplements stimulate gains. Antibiotics have been shown to be effective in stimulating rate of gain as much as 18 percent and improving the feed efficiency up to 10 percent when fed in the rations of swine. Not so conclusive evidence has been obtained, however, to show that mere inclusion of an antibiotic in a feed insures the improvement in the well-doing of the pig, unless the antibiotic is fed in adequate amounts, which is from 5.0-7.5 mg. per pound of total feed.
Keywords: Swine; Antibiotics; Protein; Sudan pasture; Gain; Feed efficiency